Survey of probable synergism between melittin and ciprofloxacin, rifampicin, and chloramphenicol against multidrug-resistant Pseudomonas aeruginosa - Sedaghati, Mahsa; Akbari, Reza; Lotfollahi Hagghi, Lida; Yousefi, Saber; Mesbahi, Tahere; Delfi, Mahdieh (Frontiers in Microbiology, 2024)
BackgroundThe emergence of multidrug-resistant bacteria and also biofilm-associated infections is a great health concern due to the failure of available antibiotics. This has alerted scientists to developing alternative antibiotics. Melittin as an antimicrobial peptide has antibacterial synergistic activity in combining with conventional antibiotics against pathogenic bacteria. Accordingly, this study aimed to assess the synergistic effect of melittin in combination with Ciprofloxacin, Rifampicin, and Chloramphenicol against MDR strains of P. aeruginosa.Materials and methodsFifty strains of P. aeruginosa were isolated from clinical specimens. The antibiotic susceptibility of isolates was evaluated by the disk diffusion method. The MIC and MBC of melittin and melittin-antibiotics combination against isolated strains were examined by microdilution method. The probable synergism between melittin and antibiotics was assayed using the FIC protocol. Time-killing kinetics and anti-biofilm effects of melittin and melittin-antibiotics combination were evaluated using time-kill kinetics and crystal violet staining method, respectively. The toxicity of the melittin-antibiotics combination on the HEK293 cell line was also assessed by the MTT assay method.ResultsOut of 50 isolates of P. aeruginosa, 15 strains are considered to be multidrug strains. Among MDR strains of P. aeruginosa, 42.85% were resistant to cefepime and ceftazidime and all urine-originate isolates were resistant to cotrimoxazole. A combination of MIC dose of ciprofloxacin and melittin decreased resistance against ciprofloxacin up to 33%. The ciprofloxacin-melittin combination showed a favorable synergism and anti-biofilm effect and was also 30.3% less toxic than melittin alone at 4 μg/ml against the HEK293 cell line. In contrast to ciprofloxacin, with the melittin-rifampicin and melittin-chloramphenicol combinations, an addition effect occurred, respectively, in 86.66 and 53.33% of MDR strains of P. aeruginosa.ConclusionCombining melittin’s antibacterial and anti-biofilm properties with traditional antibiotics may offer a novel strategy to address antibiotic resistance in P. aeruginosa. The simultaneous administration of melittin and ciprofloxacin in a single dose has shown a marked increase in antibacterial effectiveness while minimizing toxicity to the HEK293 cell line. It is advisable to conduct additional research to explore the combined antibacterial effects of melittin and ciprofloxacin in a wider range of clinical samples, animal models, and clinical trial settings.